Screening of Antibacterial and Antifungal Activities of Basidiomycetes Extracts - V. S. Lysakova; O. N. Sineva; O. P. Bychkova; L. M. Krasnopolskaya (Антибиотики и Химиотерапия, 2024)
Background. Basidiomycetes have high biosynthetic capabilities. Their metabolites are capable of exhibiting antimicrobial properties, thereby being promising molecules for use in medicine or for further chemical transformation. The aim of the work. Evaluation of antibacterial and antifungal properties of culture liquid of basidiomycetes from the orders Agaricales and Polyporales, selection of active strains for further research. Materials and methods. The objects of the study were 10 strains of 10 basidiomycetes species from the orders Agaricales and Polyporales. Filtrates of culture liquids obtained as a result of submerged cultivation of fungi, their ethyl acetate extracts and post-extraction liquids were tested. The culture liquid of Fomitopsis betulina was also extracted with chloroform and butanol. Antibacterial and antifungal eﬀects were studied by diﬀusion from wells into agar. Results. All the studied strains of basidiomycetes showed antibacterial activity. The highest activity against gram-positive and gram-negative bacteria was observed in strains of 3 species from the order Polyporales: Fomes fomentarius, F. betulina and F. pinicola. Antifungal activity was shown by 6 out of 10 studied cultures of basidiomycetes. The comparative series of extractants compiled by their eﬀectiveness (ethyl acetate > butanol > chloroform) testiﬁed to the advantage of using polar solvents to extract antimicrobial metabolites of F. betulina from the its culture liquid. Conclusion. Three promising strains of basidiomycetes — producers of antimicrobial metabolites were selected.Among the studied species, representatives of the order Polyporales showed the greatest activity. Polar solvents extracted antimicrobial metabolites of F. betulina from its culture liquid more eﬃciently than non-polar chloroform. The obtained results demonstrate the ability of basidiomycetes to produce metabolites with antimicrobial properties. It is noted that species of the order Polyporales are more active than representatives of Agaricales.